A formative study on the use of augmented reality in technical drawing courses. Issue 4 (8th December 2020) - Balak, Vehbi; Kısa, Murat; Miman, Mehmet
Abstract : Augmented reality (AR), a mixture of virtual reality and reality in a computerized virtual object mounted on real environments, has been used extensively in educational studies in recent years. This study analyzed the use of a mobile AR application (AR tool) in a technical drawing course formatively to evaluate its usefulness for 40 engineering students that failed the technical drawing course. The students who took the course a second time in a summer semester used the AR application. The AR tool brought the three-dimensional models prepared in computer-aided design. The markers or trackers where the model can be handled freely from its page were brought to the students to examine the model. The students were able to move and rotate the objects freely, and they were able to look at the objects from many angles. The results indicated that the AR tool used in the course is useful in teaching the subjects of the course. As the use of AR increased, the benefits to the students were quite positive in terms of teaching and learning. This study has shown that AR contributes greatly to the easier comprehension of technical drawings of parts that are quite complex to understand.